A Comprehensive Comparison of Various Galactic Cosmic-Ray Models to the State-of-the-art Particle and Radiation Measurements - Weihao Liu; Jingnan Guo; Yubao Wang; Tony C. Slaba (The Astrophysical Journal Supplement Series, 2024)
Galactic cosmic rays (GCRs) are the slowly varying background energetic particles that originate outside the solar system, are modulated by the heliospheric magnetic field, and pose ongoing radiation hazards to deep space exploration missions. To assess the potential radiation risk, various models have been developed to predict the GCR flux near Earth based on propagation theories and/or empirical functions. It is essential to benchmark these models by validating against the state-of-the-art measurements. In this work, a comprehensive model–observation comparison of the energy-dependent particle flux has been performed, by combining five typical GCR models and observational data from the Cosmic Ray Isotope Spectrometer on board the Advanced Composition Explorer spacecraft at relatively lower energies and data from the Payload for Antimatter Matter Exploration and Light-nuclei Astrophysics and Alpha Magnetic Spectrometer at higher energies. The analysis shows that, out of the five models investigated in this study, the optimal model, characterized by minimal relative difference or reduced chi-square divergence from measurements, depends on the particle type, energy range, and epoch of interest. Furthermore, a silicon slab is applied to compute the absorbed dose rate using conversion factors applied to GCR model outputs, and the results are compared to measurements from the Cosmic Ray Telescope for the Effects of Radiation. The comparisons in this paper have implications for the strengths and limitations of individual GCR models, advance our comprehension of the underlying GCR transport mechanisms, and also have strong application aspects for mitigating space radiation risks.